2009
DOI: 10.1016/j.jvs.2008.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for endovascular (EVAR) or open surgical repair among patients with abdominal aortic aneurysms under surveillance

Abstract: When presented with detailed information about EVAR and OSR, most patients with small aneurysms would prefer EVAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 18 publications
1
46
0
Order By: Relevance
“…Currently, patient preference is strongly in favour of endovascular repair. 230,231 However, these preferences were declared on the basis of early and mid-term evidence alone. Although there is still early mortality benefit with endovascular repair and it is a less invasive procedure than open repair, it is difficult to predict what effect these recent, long-term findings will have on patient preference.…”
Section: Graft-related Complications and Reinterventionsmentioning
confidence: 99%
“…Currently, patient preference is strongly in favour of endovascular repair. 230,231 However, these preferences were declared on the basis of early and mid-term evidence alone. Although there is still early mortality benefit with endovascular repair and it is a less invasive procedure than open repair, it is difficult to predict what effect these recent, long-term findings will have on patient preference.…”
Section: Graft-related Complications and Reinterventionsmentioning
confidence: 99%
“…19 The association between TTO and SG values in each age group differed, showing that the younger age groups were more inclined to take a risk with treatment than trading off years. The more consistent result in the oldest age group may have been influenced by their shorter life expectancy, as the quality of remaining years is valued higher, and also by the stated time horizon.…”
Section: Discussionmentioning
confidence: 98%
“…Until recently, there were no objective studies substantiating whether there was a patient preference for EVAR. However, a recent study examining patient preferences for elective future AAA repair (56) showed 84% preferred EVAR, 13% preferred open repair, and 3% could not express a preference. The results of this study support the general trend toward offering EVAR to patients in whom it is technically feasible.…”
Section: Indications and Contraindications For Evarmentioning
confidence: 99%